A research on gift practices related to marriage tradition in Kazakh Turks - Cetindag, Guelda (Milli Folklor Dergisi, 2007)
Well being of a nation depends on keeping cultural heritage alive. Turkish nation, like a treasure with its customs, traditions, morals, consuetude, beliefs and practices, life patterns, dress and finery, and kitchen etc., perpetuate its well being by carrying-on its cultural heritage for the next generations. Gift practice, one of these cultural heritages, is an expression of courtesy on events concerning individual life and social life such as birth, circumcision, ceremony of asking approval of girls' parents for marriage, engagement, marriage, and fest. Gift practice is an expression of feelings that cannot be explained and all emotions in mind and hearth are transformed to a concrete action with that. In this article it the gift practices carried out from past to today in Kazakh Turks in line with customs and traditions are presented by making comparisons with gift practices in Turkey.
Kazak Türkleri?nde evlenme gelene?i?ne ba?li olarak gerçekleşti?ri?len hedi?ye alişveri?şi? üzeri?ne bi?r i?nceleme
Keywords: culture; gift; marriage; Kazakh Turks; Turkey Turks